2023
DOI: 10.1097/jom.0000000000002945
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Sickness Absence Duration After Mild COVID-19 in a Prospective Cohort of Canadian Healthcare Workers

Anil Adisesh,
Quentin Durand-Moreau,
France Labrèche
et al.

Abstract: Objective To identify modifiable factors associated with sickness absence duration after a COVID-19 infection. Methods Participants in a prospective cohort of 4964 Canadian healthcare workers were asked how many working days they had missed after a positive COVID-19 test. Only completed episodes with absence ≤31working day and no hospital admission were included. Cox regression estimated the contribution of administrative guidelines, vaccinations, work … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…The data would also have been strengthened by a more complete history of mental ill-health prior to the pandemic with details of length and type of treatment including a longer time span than the 12 months used here. The belief that infection occurred at the workplace has been shown, in this cohort, to increase the length of sickness absence, 30 but without sequencing, there is little certainty that infection did indeed occur at work. 31 We have reported here only on the third component extracted from the ratings completed by the HCWs.…”
Section: Discussionmentioning
confidence: 75%
“…The data would also have been strengthened by a more complete history of mental ill-health prior to the pandemic with details of length and type of treatment including a longer time span than the 12 months used here. The belief that infection occurred at the workplace has been shown, in this cohort, to increase the length of sickness absence, 30 but without sequencing, there is little certainty that infection did indeed occur at work. 31 We have reported here only on the third component extracted from the ratings completed by the HCWs.…”
Section: Discussionmentioning
confidence: 75%
“…With very few hospitalisations, we were unable to assess the association between time since vaccination and severe disease; however, mild or moderate COVID-19 still has a substantial impact on society, with boosted individuals taking an average of 5 days sick leave to recover. [46] We lacked power in some subgroup analyses, particularly for asthma exacerbations, meaning that further study in larger populations is still needed to confirm or refute the associations reported. We did not have data on all of the eligibility criteria for the clinical risk group, potentially leading to some misclassification of vaccine eligibility, which may have attenuated some of our results.…”
Section: Discussionmentioning
confidence: 99%
“…Our model suggests that high levels of vaccination coverage might dilute the effect of testing on reducing absenteeism, which could be attributed to the vaccine’s efficacy in blocking infections/transmissions and resultant changes in isolation policies (after vaccination the isolation period following a positive test result could be shortened) [35]. An observational study involving a prospective cohort of 4964 HCWs in Canada showed that vaccination was strongly related to shorter absences due to COVID-19-related illness [36].…”
Section: Discussionmentioning
confidence: 99%